PENOKOHAN RANGDA DALAM NOVEL GALAU PUTRI CALON ARANG DAN JANDA DARI JIRAH - Abimardha Kurniawan (Universitas Sarjanawiyata Tamansiswa, 2020)
In the middle of 2000iest, there are two novels published that transformed from the famous Calon Arang narrative. They are Galau Putri Calon Arang (Syahrani and Yulyana, 2005) and Janda dari Jirah (Sawitri, 2007). Each work present the characterization of Rangda in different ways. The characterization aspects took as focuses in this article are (1) the character name of Rangda and (2) her genealogy. Through the comparative approach, also using the intertextuality principle, there are known that GPCA has still following the main tradition on its characterization, even it emphasizes that Rangda has a maternal relationship with Airlangga. On the contrary, JDJ gives a fresh interpretation. It stands for the massive tradition antithesis.